Numerical Investigation of Complex Thermal Coal-Gas Interactions in Coal-Gas Migration - Xiaoyan Ni; Peng Gong; Yi Xue (Advances in Civil Engineering)
Understanding the influence of temperature on the gas seepage of coal seams is helpful to achieve the efficient extraction of underground coal seam gas. Thermal coal-gas interactions involve a series of complex interactions between gas and solid coal. Although the interactions between coal and gas have been studied thoroughly, few studies have considered the temperature evolution characteristics of coal seam gas extraction under the condition of variable temperature because of the complexity of the temperature effect on gas drainage. In this study, the fully coupled transient model combines the relationship of gas flow, heat transfer, coal mass deformation, and gas migration under variable temperature conditions and represents an important nonlinear response to gas migration caused by the change of effective stress. Then, this complex model is implemented into a finite element (FE) model and solved through the numerical method. Its reliability was verified by comparing with historical data. Finally, the effect of temperature on coal permeability and gas pressure is studied. The results reveal that the gas pressure in coal fracture is generally higher than that in the matrix blocks. The higher temperature of the coal seam induces the faster increase of the gas pressure. Temperature has a great effect on the gas seepage behavior in the coal seams.